2010
DOI: 10.1387/ijdb.103198ap
|View full text |Cite
|
Sign up to set email alerts
|

Modulation of mitochondrial biogenesis and bioenergetic metabolism upon in vitro and in vivo differentiation of human ES and iPS cells

Abstract: Reprogramming somatic cells to induced pluripotent stem (iPS) cells transforms differentiated cells to an embryonic stem (ES)cell-like state characterized by the acquisition of pluripotency and self-renewal capabilities. We recently demonstrated that human ES and iPS cells share similar mitochondrial properties and bioenergetic metabolism, which are distinct from those of fibroblasts. In the present study, we have applied a global transcriptome profiling approach to compare the mitochondrial-related transcript… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

6
89
0

Year Published

2011
2011
2023
2023

Publication Types

Select...
9

Relationship

1
8

Authors

Journals

citations
Cited by 121 publications
(95 citation statements)
references
References 73 publications
(94 reference statements)
6
89
0
Order By: Relevance
“…These mitochondrial changes also impacted the cellular bioenergetic profile, which shifted from OXPHOS to glycolysis upon reprogramming and returned to OXPHOS during subsequent differentiation [18,19]. Other groups confirmed these results and showed that mitochondria within human iPSCs exhibits low oxidative stress [20] and energetic rejuvenation [21].…”
Section: Introductionmentioning
confidence: 81%
“…These mitochondrial changes also impacted the cellular bioenergetic profile, which shifted from OXPHOS to glycolysis upon reprogramming and returned to OXPHOS during subsequent differentiation [18,19]. Other groups confirmed these results and showed that mitochondria within human iPSCs exhibits low oxidative stress [20] and energetic rejuvenation [21].…”
Section: Introductionmentioning
confidence: 81%
“…Interestingly, while the close similarity between iPS cell generation and the acquisition of CSC is shedding new light on the roles of bona fide oncogenes, tumor suppressor genes, transcription factors and chromatin regulators, in mediating the transition from differentiated-to-stem cell states in cancer tissues, an increasing number of experimental studies have consistently revealed that, similar to embryonic and adult stem cells, iPS cells are metabolically distinct from their differentiated counterparts. [25][26][27][28][29][30][31][32] Moreover, the precise metabolic properties of stem cells appear to be functionally relevant for stem cell identity and specification regardless of their cellular sizes or cell duplication dynamics, implicating a metabolism-centric regulation of stemness and cell fate.…”
Section: Metabolic Control Of Cancer Cell Stemness: Lessons From Ips mentioning
confidence: 99%
“…[33][34][35][36][37][38][39][40][41][42][43][44][45][46][47] Similar to well-recognized genetic and epigenetic factors, OXPHOS-to-glycolysis bioenergetic resetting appears to operate as a crucial enabling regulator of nuclear reprogramming because the self-renewal and pluripotency attributes cannot be efficiently acquired in the presence of an inadequate bioenergetic metabotype. Thus, efficiency of reprogramming is greater the closer the glycolytic/OXPHOS energy metabolism profiles of the starting somatic cells are to those of embryonic stem cells (ESC).…”
Section: Metabolism and Cancer Stemness: Lessons From Ips Cellsmentioning
confidence: 99%
“…Thus, a Warburg-like metabolic shift of somatic oxidative energy metabolism to a glycolytic metabotype promotes proficient reprogramming, establishing a novel regulator of acquired stemness. [36][37][38][39][40][41][42] Given that (1) Many tumor cells have developed mechanisms to escape the growth-restraining effects imposed by the switching of cellular metabolism from anabolic to catabolic modes that occur upon activation of the energy sensor adenosine monophosphate (AMP)-activated protein kinase (AMPK); [43][44][45][46][47] (2) AMPK is activated by the antidiabetic drug metformin and many natural products, including "nutraceuticals" and compounds used in traditional medicines, [45][46][47][48][49] and (3) AMPK activators potentially have cancer preventative effects, and there is already evidence that metformin usage provides protection against the initiation of several human cancers, [50][51][52][53][54] we hypothesize that AMPK might be an "energy checkpoint" that closely regulates the energetically demanding reprogramming process. Taking advantage of the iPSC-based model, which suggests that inducing a differentiated somatic cell to become more stem-like Figure 1 (See previous page).…”
Section: Metformin Impedes the Somatic Reprogramming Of Mouse Embryonmentioning
confidence: 99%